A meta-analysis of the association of CKM gene rs8111989 polymorphism with sport performance - Chen, C.; Sun, Y.; Liang, H.; Yu, D.; Hu, S. (Biology of Sport, 2017)
The muscle-specific creatine kinase (CKM) A/G variants (rs8111989) have been associated with skeletal muscle performance in humans; they are correlated with physical performance and contribute to differences in the maximum oxygen uptake (VO2max) responses during power or endurance training. However, there is not enough definitive evidence to demonstrate whether the A and G allelic variants of the CKM gene rs8111989 are indeed genetic factors that can influence human physical performance. In our study, we identified 9 articles on CKM in a literature search, and conducted two meta-analyses on the CKM rs8111989 A/G allele or genotype differences between power or endurance athletes and general controls. We found that the power athletes had a significantly higher frequency of the G allele (OR, 1.14; 95% CI, 1.02-1.28, P=0.03) and GG genotype (OR, 1.54; 95% CI, 1.24-1.91, P<0.0001) compared to controls, but there was no significant difference for the endurance athletes (G allele, OR, 0.95, 95%CI, 0.85-1.06, P=0.34; GG genotype, OR, 1.00, 95%CI, 0.78-1.27, P=1.00). The results provide additional evidence to support the notion that human physical performance might be influenced by genetic profiles, especially in power sports.